1994
DOI: 10.1210/jcem.79.1.8027259
|View full text |Cite
|
Sign up to set email alerts
|

Roles of insulin resistance and beta-cell dysfunction in the pathogenesis of glucose intolerance in cystic fibrosis.

Abstract: The roles of insulin deficiency and insulin resistance in the pathogenesis of glucose intolerance in cystic fibrosis (CF) were evaluated in eight patients (aged 16.5 +/- 1.9 yr), four with normal glucose tolerance (NGT) and four with impaired glucose tolerance (IGT), and in seven healthy control (CN) subjects. First and second phase insulin secretions were evaluated during a hyperglycemic clamp. Hepatic glucose production (HGP) and insulin-stimulated glucose disposal were measured using [6,6-2H2]glucose and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The higher levels of glucose in the initial part of the OGTT may provide an increased stimulus to increased insulin secretion later in the OGTT and hence the normalization of the 2-h glucose value. Physiological studies looking at firstand second-phase insulin studies using intravenous glucose tolerance tests and hyperglycaemic clamps support this hypothesis [25,33,35,36].…”
Section: Cgms Resultsmentioning
confidence: 89%
“…The higher levels of glucose in the initial part of the OGTT may provide an increased stimulus to increased insulin secretion later in the OGTT and hence the normalization of the 2-h glucose value. Physiological studies looking at firstand second-phase insulin studies using intravenous glucose tolerance tests and hyperglycaemic clamps support this hypothesis [25,33,35,36].…”
Section: Cgms Resultsmentioning
confidence: 89%
“…Although studies in CF subjects with normal glucose tolerance (NGT) have shown normal insulin sensitivity, there are conflicting reports regarding its role in patients with impaired glucose tolerance (IGT) and CFRD since studies have shown increased [5,6], normal [7][8][9] or decreased insulin sensitivity [10][11][12][13][14]. The disagreement among previous studies relates to differences in inclusion criteria [7,11], age distribution [10,12], small patient numbers [6,10] and interpretation of results [12,14]. Another contributory factor to the discordant findings stems from a variety of methods used to measure insulin resistance [5,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…1 Patients with CF are also susceptible to insulin resistance that may worsen with steroid therapy, pulmonary infections and poor nutrition. 2,3 The effect of hyperglycaemia on outcomes following bilateral lung transplantation in CF patients is not known, but is assumed to be associated with increased mortality as seen in the general medical setting. 4 More specifically, it is not known whether a prior diagnosis of CFRD affects outcomes over and above that of inpatient hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%